Organizational Cynicism and Deviance Work Behaviour in the Banking Sector: Investigating the Role of Work-Life Balance and Perceived Organizational Support as Mediators - Sajuyigbe, Ademola Samuel; Sanusi, Bolanle Mistura; Babalola, Olusola Adebola; Akinbobola, Abiola Olubunmi; Tella, Adeniran Rahman; Obi, Nwoye James (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2025)
Objective: This study explores the mediating roles of work-life balance (WLB) and perceived organizational support (POS) in the relationship between organizational cynicism (OC) and deviant work behaviours (DWB) in Nigerian banks. It extends the application of Organizational Justice Theory and Leader-Member Exchange (LMX) Theory to the banking sector, highlighting their relevance in understanding employee behaviour within high-pressure organizational settings. Design/Methods/Approach: The data were collected through a survey questionnaire administered to 120 bank employees. Data analysis was conducted using Path Analysis Structural Equation Modelling (PA-SEM). Findings: The study indicates that organizational cynicism significantly contributes to deviant workplace behaviours, driven by factors such as poor leadership, lack of transparency, unrealistic targets, and job insecurity. However, both work-life balance and perceived organizational support were found to have a negative and significant impact on workplace deviance, indicating that better work-life balance and higher organizational support are associated with reduced employee misconduct. Moreover, mediation analysis confirms that WLB and POS partially mediate the OC-DWB relationship, suggesting that reducing cynicism alone is insufficient; organizations must also enhance employee well-being and foster a supportive work culture. Originality/Value: The study advances theoretical knowledge by demonstrating the partial mediating mechanisms through which organizational cynicism translates into deviance, and highlights the significance of social exchange dynamics and perceptions of fairness in shaping employee behaviour. Practical/Policy implication: The findings underscore the need for banking institutions and policymakers to go beyond surface-level interventions aimed at reducing cynicism. To effectively curb deviant workplace behaviours, organizations should implement comprehensive strategies that promote work-life integration, enhance organizational support systems, and cultivate ethical and transparent leadership.